The protective effect of alpha lipoic acid against traumatic brain injury in rats - VELİOĞLU ÖĞÜNÇ, AYLİZ (TAYLOR & FRANCIS LTD, 2009)
Traumatic brain injury (TBI) was induced by a weight-drop device using 300 g-1 m weight-height impact. The study groups were: control, alpha-lipoic acid (LA) (100 mg/kg, po), TBI, and TBI + LA (100 mg/kg, po). Forty-eight hours after the injury, neurological scores were measured and brain samples were taken for histological examination or determination of thiobarbituric acid reactive substances (TBARS) and glutathione (GSH) levels, myeloperoxidase (MPO) and Na+-K+ ATPase activities, whereas cytokines (TNF-, IL-1) were determined in blood. Brain oedema was evaluated by wet-dry weight method and blood-brain barrier (BBB) permeability was evaluated by Evans Blue (EB) extravasation. As a result, neurological scores mildly increased in trauma groups. Moreover, TBI caused a significant decrease in brain GSH and Na+-K+ ATPase activity, which was accompanied with significant increases in TBARS level, MPO activity and plasma proinflammatory cytokines. LA treatment reversed all these biochemical indices as well as histopathological alterations. TBI also caused a significant increase in brain water content and EB extravasation which were partially reversed by LA treatment. These findings suggest that LA exerts neuroprotection by preserving BBB permeability and by reducing brain oedema probably by its anti-inflammatory and antioxidant properties in the TBI model.
Keywords: Alpha lipoic acid; brain injury; closed head; trauma; blood-brain barrier; oedema; ISCHEMIA-REPERFUSION INJURY; CLOSED-HEAD INJURY; OXIDATIVE STRESS; REACTIVE OXYGEN; NA+,K+-ATPASE ACTIVITY; METABOLIC ANTIOXIDANT; MELATONIN; MODEL; PATHOPHYSIOLOGY; NEUROPROTECTION